The use of interactive teaching methods in the training of sports coaches in universities in China - Zhai, X.; Ryzhkova, L. G.; Go, E. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the level of demand for interactive teaching methods when conducting classes aimed at acquiring special knowledge, professional skills and abilities from future table tennis coaches.